2005
DOI: 10.1242/jeb.01690
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cortisol administration on social status and brain monoaminergic activity in rainbow troutOncorhynchus mykiss

Abstract: SUMMARY The hypothesis that circulating cortisol levels influence the outcome of social interactions in rainbow trout was tested. Juvenile rainbow trout Oncorhynchus mykiss were given a single intraperitoneal (i.p.)implant containing either cortisol (110 mg kg–1 fish), or cortisol plus the glucocorticoid receptor antagonist RU486 (mifepristone; 1100 mg kg–1 fish), and sampled after 5 days of social interactions with either a similar sized (<1.5% difference in fork length)or smaller conspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(85 citation statements)
references
References 78 publications
(84 reference statements)
4
77
0
4
Order By: Relevance
“…It was later shown that rapid resumption of feeding following transfer to a novel environment also predicts social dominance and level of aggression towards territorial intruders in non-selected aquaculture strains of rainbow trout (Øverli et al, 2004;Schjolden et al, 2005a). Most of the behavioural characteristics of the HR line are consistent with previously reported effects of the steroid hormone cortisol in non-mammalian vertebrates (Gregory and Wood, 1999;Øverli et al, 2002b;DiBattista et al, 2005). However, it seems unlikely that cortisol alone is responsible for controlling all behavioural aspects of stress coping style (Koolhaas et al, 2007;Øverli et al, 2007).…”
Section: Walbaum 1792)supporting
confidence: 75%
“…It was later shown that rapid resumption of feeding following transfer to a novel environment also predicts social dominance and level of aggression towards territorial intruders in non-selected aquaculture strains of rainbow trout (Øverli et al, 2004;Schjolden et al, 2005a). Most of the behavioural characteristics of the HR line are consistent with previously reported effects of the steroid hormone cortisol in non-mammalian vertebrates (Gregory and Wood, 1999;Øverli et al, 2002b;DiBattista et al, 2005). However, it seems unlikely that cortisol alone is responsible for controlling all behavioural aspects of stress coping style (Koolhaas et al, 2007;Øverli et al, 2007).…”
Section: Walbaum 1792)supporting
confidence: 75%
“…For instance, it has been shown in mammals that 5HT stimulates CRF release by the hypothalamus (Boisvert et al, 2011;Calogero et al, 1989) and also ACTH release by the pituitary (Calogero et al, 1993). Additionally, serotonergic activity is affected by other elements of the stress response such as cortisol, CRF or AVT (DiBattista et al, 2005;Dinan, 1996;Price and Lucki, 2001;Sangiao-Alvarellos et al, 2004;Summers et al, 2005). Therefore, we consider that studying the temporal pattern of activation of serotonergic signaling after exposure to a stressor is of vital importance to understanding the participation of the brain serotonergic system in the integrated stress response.…”
Section: Discussionmentioning
confidence: 99%
“…The scoring scheme was similar to that used previously for assigning social status to pairs of rainbow trout (e.g. DiBattista et al 2005DiBattista et al , 2006 and assigns higher scores to more dominant behaviours. A single behaviour score was calculated from all observations with a principal components analysis, and the fish with the higher overall behaviour score within each pair was assigned dominant social status.…”
Section: Methodsmentioning
confidence: 99%